Penguatan Good Manufacturing Practices (GMP) pada CV. Pawon Ibun dalam rangka Mempersiapkan Sertifikasi pangan. - Shafira Enri Shalsabiella; Yulistiani, Ratna; Fauziyah, Nur Aini (Journal of Science and Social Development, 2024)
Currently, there are many problems regarding the quality and safety of products that can endanger consumers. GMP (Good Manufacturing Practices) is a fun way in the form of application in the food processing industry to guarantee and ensure the safety and quality of the products produced. The purpose of this community service is to conduct training application (Good Manufacturing Practices) of GMP on CV. Pawon Ibun in order to prepare for Food certification CV. Pawon Ibun is a business engaged in food processing that specifically produces MPASI for baby and toddlers. In addition to the aim of obtaining food certification, another objective of the training and assistance provided to workers is to provide an understanding of the importance of GMP and be able to apply it during the production process, so that CV. Pawon Ibun is able to produce safe and quality processed food. The research method used is a qualitative approach and survey methods are also used in data collection. Implementation starts from training, mentoring and also evaluation. Based on the survey results, it can be seen that the employees of CV. Most of Pawon Ibun did not know about and had not received training on GMP. And after receiving training, they are able to understand the concepts, objectives, and benefits of GMP and are able to apply them during the production process. That way, CV. Pawon Ibun is eligible to get GMP food certification.